Regenerative Endodontic Therapy using a New Antibacterial Root Canal Cleanser in necrotic immature permanent teeth: Report of two cases treated in a single appointment. Issue 4 (11th March 2021) - Pace, R; Giuliani, V; Di Nasso, L; Pagavino, G; Franceschi, D; Franchi, L
Abstract : A case of regenerative endodontics: (a) before treatment; (b) post‐treatment Xray; (c) follow‐up at 6 months; (d) follow‐up at 12 months.